2014 IEEE International Energy Conference (ENERGYCON) 2014
DOI: 10.1109/energycon.2014.6850481
|View full text |Cite
|
Sign up to set email alerts
|

The stochastic approach for conductor selection in transmission line development projects

Abstract: A stochastic approach is proposed for selecting the overhead line cross-sections that would be optimal taking into account the electricity market conditions. For this purpose, several conductor types with different conductor cross-sections were considered including the High Temperature Low Sag conductor types such as ACCC and ACCR, which are a part of the advanced technology. The total capital costs depending on the technical aspects were estimated as well. The paper proposes a method that minimizes the averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Effective capacitor placement, which aids in loss reduction, is highlighted in various papers such as [36], [50], [88]. Some studies have also focused on cost minimization for transmission lines, illustrated in [93], and enhancing reliability by reducing losses, as seen in [146]. Additional research on minimizing energy loss costs can be found in [75] and [77].…”
Section: Economic Objectivesmentioning
confidence: 99%
“…Effective capacitor placement, which aids in loss reduction, is highlighted in various papers such as [36], [50], [88]. Some studies have also focused on cost minimization for transmission lines, illustrated in [93], and enhancing reliability by reducing losses, as seen in [146]. Additional research on minimizing energy loss costs can be found in [75] and [77].…”
Section: Economic Objectivesmentioning
confidence: 99%
“…Studies devoted to the optimization problem of minimizing the capital costs of a TL with respect to the selection of the optimum cross-sectional area of the conductor applied deterministic [15,16] and stochastic methods. For instance, the proposed stochastic approach to selecting the conductor cross-section, which takes into account random variables such as the power line load, electricity price, and ambient temperature, was presented in References [17][18][19]; the method of selecting the conductor and tower configuration from an overall system point of view was considered in Reference [20]; and the methodology for selecting both bare wire conductors and ground wires, their spatial arrangement, and the topology of the tower for a project with compact overhead transmission lines with multiple circuits was presented in Reference [21].…”
Section: Introductionmentioning
confidence: 99%
“…It means that there are no unique exact optimization techniques. Thus, there are two basic categories: deterministic (classical) methods and stochastic methods [1], [18]- [20]. The existing deterministic approaches are simpler, however, they make several assumptions that neglect the fluctuations of the energy prices and are based on the deterministic statements and a rough approximation of the electrical loads.…”
Section: Introductionmentioning
confidence: 99%